A sound brand identity design: The interplay between sound symbolism and typography on brand attitude and memory. (January 2022) - Jun, Yesel; Lee, Hyunju
Abstract: A growing body of research testifies that humans naturally deduce certain images from auditory cues as they do from visual cues. In the context of branding, this paper bridges two streams of research to reveal how the interplay between the auditory and visual images embedded in brand identities influences consumer response. Study participants were exposed to brand logotypes whose brand name and typography either agree or disagree in the images they convey. The results revealed that audiovisual image congruence in brand identity leads to increased brand appeal and quality perception as well as memory. In addition, the effect of auditory images and that of visual images were found to equally influence associative mappings such that neither dominates the other. These findings provide an evidential ground to reason and further explore how business enterprises may effectively communicate their brand images through multisensory channels by providing guidance in the intuitive decision-making process involved in brand naming and visual identity development.